Justice, equity, diversity, and inclusion in education : school-university-community research - Reardon, R. Martin; Leonard, Jack, 1948- (Current perspectives on school/university/community research., 2024)
"As Dr. Martin Luther King, Jr. intimated in his speech in the National Cathedral (March 31, 1968), there is sense of moving towards-of journeying-rather than arriving in the context of justice (and, I would add, equity, diversity, and inclusion). We who embark on this journey are incomplete-not fully formed, despite our amazing competence in so many ways. We are travelers in the fashion of the figure in Catalano's KHADINE sculpture (https://brunocatalano.com/sculptures_/KHADINE-a-Londres), gazing unfazed on a world of superlative human achievements, clasping our bag firmly in one hand even though there is something missing in our core. In fact, as in KHADINE, our bag holds us together individually but, in relationship to our fellow travelers, our baggage holds us apart"-- Provided by publisher.